Design of an M-Commerce mobile application to reduce the cessation of operations of textile companies due to the social isolation generated by SARS-CoV-2 in Peru - Dávila Asto, Johan Jesús (2022)
This research includes the design of an M-Commerce application to reduce the cessation of operations of textile companies in Lima-Peru; due to the SARS-CoV-2 health emergency declared in the country. Being the objective of this investigation, to reduce the cessation of the textile companies affected in their sales and processes. This technological design allows entrepreneurs to offer their products, control sales, profits and reduce order service times through the mobile application. The research methodology is applied, and a pre-experimental design was considered that measures the registration time of generating orders, the quality of the orders and the follow-up. Two companies from the Gamarra Shopping Center were used as samples, to whom a pre-test and post-test were applied; obtaining as a result, in the indicator, time of registration of orders generated, an average time reduction of eight minutes. Likewise, for the quality indicator of generating orders, an average growth of 19.05% was obtained. Finally, for the order tracking indicator, an increase in the satisfaction of the order process was obtained.